The neuroevolution of empathy - Decety, Jean (Annals of the New York Academy of Sciences, 2011)
There is strong evidence that empathy has deep evolutionary, biochemical, and neurological underpinnings. Even the most advanced forms of empathy in humans are built on more basic forms and remain connected to core mechanisms associated with affective communication, social attachment, and parental care. Social neuroscience has begun to examine the neurobiological mechanisms that instantiate empathy, especially in response to signals of distress and pain, and how certain dispositional and contextual moderators modulate its experience. Functional neuroimaging studies document a circuit that responds to the perception of others’ distress. Activation of this circuit reflects an aversive response in the observer, and this information may act as a trigger to inhibit aggression or prompt motivation to help. Moreover, empathy in humans is assisted by other domain‐general high‐level cognitive abilities, such as executive functions, mentalizing, and language, which expand the range of behaviors that can be driven by empathy.